ANALISIS YURIDIS TINDAKAN SEPIHAK PENGUBAHAN THRESHOLD DEVELOPMENT TAXONOMY NEGARA BERKEMBANG ANGGOTA WORLD TRADE ORGANIZATION OLEH UNITED STATES TRADE REPRESENTATIVE - Kent Kurniawan Handi; Wisnu Aryo Dewanto (Fakultas Hukum Universitas Kristen Indonesia, 2020)
In its efforts to protect the national economy the power of a country is not unlimited. The state, as the holder of sovereignty, must comply with the provisions of international law. As a WTO member who also ratified the GATT, Enabling Clause, Marrakesh Agreement, and Doha Declaration, United States of America should have complied with, and implemented with full commitment, all the provisions governed in these agreements. On the basis of the order issued by President Donald Trump through a memo dated July 26, 2019, on February 10, 2020 USTR announced a new development taxonomy threshold that caused Indonesia and 22 other WTO member countries with Gross National Income per capita less than US 12,375.-, the threshold of the World Bank's high-income countries, to involuntarily lose their status as developing countries, which resulted in these countries being deprived access to WTO’s special and differential treatment provisions. The purpose of this paper is to conduct a juridical analysis on the unilateral action taken by USTR to alter the development taxonomy threshold of WTO’s developing country members examined from the concept of